KONSEP MARKETING DALAM INOVASI PRODUK PERBANKAN SYARIAH - Himyar Pasrizal (Institut Agama Islam Negeri Batusangkar, 2018)
Business andbankingcompetitiongetting tougher anddynamicwith the flowof modernity, in which thebankis nownot onlysavespacebutalso asa place for investmentand financial consultingmakingbanking productsinIndonesiaincreasingly variedtomeet those needs. Product innovationis akeystone tothe methodof product development. Product innovationcan deliverthe product to berepackagedor new products. Product innovationis also donethrough theimprovement orrefinementof existing products, adding features,specifications andthe resultingbenefits. Islamic bankingshouldbe careful inproductinnovationso that the demandfor the productremains high. This meansnotonlyproduct innovationbut ratherproduct orientedto customeroriented.In other words,the development ofinnovativeIslamic bankingproductsis consistent with therequirements(needs) and desires(wants) ortastecurrentcustomers. Whichis more important inmarketingandproduct innovationin Islamic bankingishow theproductand the productinnovationis not contrary toIslamic lawor contrary tothe Qur'an andSunnah. Product innovationmust be donewhenthe position ofthe PLCisin decline sales.